Natural remedies in the Canon of Medicine for dentistry and oral biology - Pouya Faridi; Milad Moatamedi; Mohammad M Zarshenas; Zohreh Abolhassanzadeh; Abdolali Mohagheghzadeh (Shiraz University of Medical Sciences, 2015)
Ibn Sina is one of the most well know scholars in middle ages. This Persian physician wrote different books in medical filed which his great encyclopedia remained as one the most successful medical encyclopedia during the history. Ibn Sina discussed diseases of oral cavity and dentistry in the 3rd book of The Canon of medicine. He discussed different conditions such as different types of trauma to the motor nerves, taste sensation, different limitations of tongue movements, Ranula, halitosis, tooth sensation, different types of tooth pain, Bruxism, attrition, loss of enamel, gingival bleeding, recession and hyperplasia. For management of these diseases he introduced more than 80 herbal remedies. Most of this plant species are from essential oil reach families. Generally, Ibn Sina has a deep view in case of dental diseases and his ideas and methods for treatment of this category of disease could be studied for finding new treatment in dental ailments.